(untitled) (The Agriculturists, 2012)
The investigation was carried out to evaluate the effect of different organic manures on turmeric with reference to vegetative growth, biomass production, rhizome yield and its attributes of turmeric (Curcuma longa L.). Turmeric showed better response to the application of organic manures. Plant with neem cake application had the taller plant (79.30 cm), maximum number of tillers per plant (5.40), leaf number (5.40), leaf area (44.09) leaf area index (0.429), fresh weight of halum ( 190.05g), fresh weight of root (49.13 g), fresh weight of rhizome per plant (256.21 g) and dry weight of halum (15.21g), dry weight of root (7.32 g), dry weight of rhizome per plant (40.35 g), total dry matter yield (6.85 t ha-1) than those received other types of manures. Moreover, yield attributes such as number of mother rhizomes per plant-1 (1.75), more number of primary rhizomes per plant-1 (5.19), secondary rhizomes per plant-1 (18.03) and tertiary rhizomes per plant (7.69) were also highly accelerated by neem cake application. Similarly, the same treatment expressed the best in terms of size of mother rhizome (7.69 cm), primary rhizome (21.86 cm) and secondary rhizomes (7.05 cm).All these parameters in cumulative contributed to produce the highest estimated fresh rhizomes yield & cured rhizomes yield (29.48 t ha-1, 5.59 t ha-1 respectively). The highest curing percentage (20.28) was observed in T3 treatment having mustard cake@ 2.0 t/ha. Thus, organic manure like neem cake was best fitted natural fertilizer for turmeric cultivation. DOI: http://dx.doi.org/10.3329/agric.v10i1.11060 The Agriculturists 2012; 10(1): 16-22